Study of risk factors and symptoms variation in renal cell carcinoma patients - الديب باسل; محمد كنعان; لؤي نداف (Latakia University Journal -Medical Sciences Series, 2022)
Renal cell carcinoma is the most common malignancy of the kidney,and considers the thirteenth most common cancer in the world Several epidemiological studies have been conducted, aimed to refute the factors that cause or increase the risk of renal cell carcinoma in addition to describe the different clinical symptoms. Purpose : Research in our society about the prevalent risk factors and their related with the increased incidence of renal cell carcinoma , and study of the clinical symptoms and their differences in patients with renal cell cancer. Patients and methods: This is a retrospective case-controle study for A group of patients with renal cell carcinoma were performed in the Urology Department of thishreen hospital Within the period from 2016 to 2021,and Compare it with a group of healthy controls, those controls did not have renal cell carcinoma. The study included 264 people(88patients with Rcc and 176 controls). A statistical study was conducted for the risk factors (gender, age, smoking, hypertension, diabetes mellitus, drug exposure to alpha blockers).and display the results using range , median, mode, frequency, percentage and percent of total using chi-square test for p Values. Results: 88 patients with RCC were , 51 males and 37 females, the incidence in males is greater than females by 1:1.3,with is no statistically significant difference between the sexes,Ages rang was between 30-80 with an average age of 57 years. Patients were distributed into age groups. The peak incidence of injuries was observed from 50 to 70 years.and about the diagnostic conditions, the percentage of asymptomatic diagnoses (by chance) in our study was (26%), the largest number of patients diagnosed by chance was recorded in 2018 (9) patients s in the symptomatic patients hematouria was the most frequencies s(74%), while flank pain (66%), fever (23%) weight loos (46%) varicoceles (3%) By studying the risk factors, it was found that : smoking is associated with Rcc (p-value =0.0004) and RR=4175 in confidence I 95% [1.203-1.669] It was found that there is an important indication of the association between hypertension and Rcc (P-value 0168) and RR=1.2968 in CI 95%[1.021-1.651] We found significant statistical significance for the association between diabetes mellitus( p-value =0.043) and RR=1.145 in CI 95%[1.328-0.9877] The study showed an association between taking alpha-blockers and Rcc(p-value=0.044) and RR=1.188 in CI 95% [0.09944-1.4207] conclusion: - The risk of developing renal cell carcinoma increases with age, especially at ages over 50 years, with a peak incidence at age 55. the incidence of males: females reached 1:1.3 with an increased risk in males at a rate of 1.5%. - Smoking increases the incidence of RCC by 41.75%, with an important relationship in females, where smokers are 8 times more likely to be infected than non-smokers. - Hypertension increases the risk of incidence by an average of 29.7%, and diabetes also increases the risk by an average of 14%. - The rate of asymptomatic diagnoses in our study was 26%,While hematuria was the most common symptom in patients by 74% Followed by flank pain 66%, palpable mass 22%.